Hypothetical 3D reconstruction of the tomb of the nomarch Ini from Gebelein - Wojciech Ejsmond; Jakub Stępnik (Polish Archaeology in the Mediterranean)
The paper presents a hypothetical reconstruction of the tomb of a provincial dignitary, Nomarch (district governor) Ini I, who lived during the First Intermediate Period (late 3rd millennium BCE) and was buried in the Northern Necropolis of Gebelein. The tomb was discovered by Virginio Rosa in 1911. An unpublished account of the tomb’s discovery offers exact dimensions and a detailed description allowing to propose a reconstruction of its form and furnishing. Blender, an open-source software designed for three-dimensional modeling, has been employed for the task. The modeling process is described and followed by a discussion of the validity and usefulness of such reconstructions for archaeology and dissemination of research results.